(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Systemic sclerosis (SSc) is a multisystem autoimmune connective tissue disorder characterized by fibrosis, vasculopathy, and immune dysregulation. Distal renal tubular acidosis (dRTA) is an uncommon manifestation and may rarely present with life-threatening electrolyte abnormalities. Aim & Objectives: To report a rare case of systemic sclerosis–Sjögren overlap syndrome presenting with distal renal tubular acidosis and severe hypokalemia. To highlight the importance of early recognition of autoimmune causes of unexplained metabolic acidosis and the role of prompt diagnosis and appropriate immunosuppressive management in improving clinical outcomes. Case Presentation: A 58-year-old woman with a history of type 2 diabetes mellitus and hypothyroidism presented with acute respiratory distress, hypoxia, hypotension, and generalized limb weakness. She required intensive care unit admission and ventilatory support. Initial investigations revealed severe hypokalemia and metabolic acidosis. Further evaluation demonstrated a positive urine anion gap consistent with distal renal tubular acidosis. Autoimmune workup showed positivity for antinuclear antibodies, anti-Scl-70, anti-SSA, and Ro-52 antibodies. Skin biopsy confirmed systemic sclerosis with Sjögren overlap syndrome. Additional investigations revealed interstitial lung disease with a nonspecific interstitial pneumonia pattern, esophageal dysmotility, vocal cord paralysis, and proteinuria, indicating extensive multisystem involvement. The patient was treated with correction of electrolyte abnormalities, corticosteroids, immunosuppressive therapy, and supportive care. Significant clinical improvement was observed with normalization of serum potassium levels and recovery from respiratory and hemodynamic compromise. Results: A 58-year-old woman with systemic sclerosis–Sjögren overlap syndrome presented with distal renal tubular acidosis, severe hypokalemia, and metabolic acidosis causing respiratory failure and hypotension. Treatment with electrolyte correction, corticosteroids, immunosuppressants, and supportive care resulted in normalization of serum potassium, resolution of acidosis, and significant clinical recovery. Conclusion: This case highlights a rare presentation of systemic sclerosis with Sjögren overlap syndrome manifesting as distal renal tubular acidosis and severe hypokalemia. Early recognition of autoimmune causes of unexplained metabolic acidosis and hypokalemia is essential for timely diagnosis and appropriate management.